Beta-thalassemia mutation types and the relationship with the demographic factors in Sanliurfa, Turkey - Ebru Tuncez; Özlem Öz; Burcu Akıncı; Fatma Demir (SERNEV, 2021)
Introduction: Beta-thalassemia is an autosomal recessive disease that occurs as a result of a disorder in the (β-globin chains synthesis), and the gold standard method for diagnosis is genetic mutation analysis. It is important to know the distribution of mutations according to regions and races. The aim of this study is to document the mutations in the beta-globin gene of beta-thalassemia major and intermedia patients who were followed and treated in Sanliurfa province, and to examine the relationships between these mutations by defining them according to gender, nationality, consanguineous marriage, history of disease in siblings and blood type.Methods: The files of 272 patients diagnosed with beta-thalassemia major and intermedia followed up in the Pediatric Hematology-Oncology outpatient clinic of Sanliurfa Training and Research Hospital between August 2016 and August 2017 were retrospectively reviewed and mutation analyzes were documented. Coding exons and exon-intron junction regions of beta globin-HBB gene were amplified by PCR method and then DNA sequencing was performed. Gender, nationality, consanguineous marriage, sibling history and blood type information were recorded.Results: Out of 272 patients, 94.1% were thalassemia major and the others were thalassemia intermedia. Approximately one third of the patients (30.1%) were foreign nationals. A total of 27 different mutations in the beta-globin gene were detected. The most common mutation is IVS-I-110 c.93-21 (G gt; A) (23.1%), which is followed by IVS-I-1 c.92 + 1 (G gt; A) (15.8%) and Codon 39 c.118 (C gt; T) (11.5%). One hundred and forty-two individuals (52.2%) had no sibling history, while 103 (37.9%) had one sibling and 27 (9.9%) had two siblings with thalassemia disorder. First-degree, second degree and third degree consanguineous marriages were present in 42.6% (n = 116), 8.1% (n = 22), 11% (n = 30) of parents, respectively.Conclusions: Beta-thalassemia disease is a common hematological condition in Sanliurfa. Approximately one-third of the patients who apply are foreign nationals. Correct identification of beta-globin gene mutations will guide genetic counseling and preventing prenatal disease. This data can contribute to the national thalassemia prevention program in Turkey.